Estimation of the thermal resistance of snow cover based on the ground temperature - V. M. Kotlyakov; A. V. Sosnovsky (Лëд и снег, 2021)
Climate changes have influence on the thermal stability of permafrost soils. The assessment of its changes should be made taking account of the parameters of the snow cover and its thermophysical characteristics. A method for determining the thermal resistance of snow cover and the effective coefficient of thermal conductivity of snow based on ground temperature is proposed for areas of the Arctic zone of the Russian Federation with negative ground temperatures. From data on ground temperature measurements at depths of 20 and 40 cm obtained from hydrometeorological stations, it is possible to estimate the heat flow from the ground into the snow cover and, at a known air temperature and snow depth, to calculate the thermal resistance of the snow and the effective coefficient of thermal conductivity. In this case, the obtained value of the thermal conductivity coefficient of snow will include all the features of the snow cover development by the time of measurement. To develop a method for determining the thermal resistance of snow cover and the effective coefficient of thermal conductivity of snow, numerical experiments were performed using a mathematical model, which allowed establishing the conditions for the applicability of the method. The paper presents results of calculations of the thermal resistance and thermal conductivity of snow cover made by the proposed method for winters of 2006/07 and 2009/10 in Yakutia for the snow cover of different thickness composed mainly by semi-skeletal and skeletal crystals of deep frost, reaching a diameter of 3–5 mm. The use of this method for the conditions of the Yakutsk with a known type of snow formation confirmed its effectiveness.